A second new species of Nanophyllium Redtenbacher, 1906 from the northern coast of New Guinea (Phasmida, Phylliidae) - Cumming, Royce T. (Zootaxa, 2017)
A new species of leaf insect, Nanophyllium larssoni n. sp. is described and illustrated bringing the known species in the genus to a total of six. Like all species of Nanophyllium Redtenbacher, 1906, the new species is named from a single male specimen, which is deposited in the San Diego Natural History Museum. With this newly identified species, two clear species-groups emerge and are described, in detail, in the species key. Measurements of anatomical figures were made to the nearest 0.1 mm.